Professionalism of Junior High School Teachers' Performance in the Learning Process: Pedagogical Competency Analysis - Epin Candra Buana; Ebtaniz Zulwidyaningtyas; Anang Sulistyo (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background: Teacher professionalism, particularly in pedagogical competence, plays a critical role in the quality of the learning process and student outcomes. Understanding how teachers apply and develop their pedagogical skills is essential for enhancing educational effectiveness. Objective: This study aims to assess the professionalism of teacher performance in the learning process at SMP Negeri 1 Kepung, with a specific focus on pedagogical competence. Method: A qualitative-descriptive approach was employed. Data were gathered through observations, interviews, and documentation involving teachers and the principal. The data analysis process included data reduction, presentation, verification, and conclusion drawing. Result: The study identified three key aspects of pedagogical competence among teachers: (1) efforts to improve students' abilities, (2) effective performance during the learning process, and (3) strategic approaches to developing pedagogical skills. Conclusion: Teachers at SMP Negeri 1 Kepung exhibit professional pedagogical competence through various strategies aimed at improving student learning and instructional quality.Contribution: This study offers both theoretical and practical contributions by providing insights into the development of teacher professionalism, serving as a reference for future educational practices and policy improvements related to pedagogical competence.